Editorial – War in Sudan: The Impact on Maternal and Perinatal Health - Ahmed A Hassan; Ishag Adam; Nazik Elmalaika Husain (Sudan Journal of Medical Sciences)
This is an Editorial and does not have an abstract. Please download the PDF or view the article in HTML.